2007
DOI: 10.1002/pds.1400
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and quality of adverse drug reaction reports by pharmacists in Norway

Abstract: Pharmacists submit valuable ADR reports which provide information complimentary to physicians' reports. This emphasises that pharmacist ADR reporting might constitute an important addition to the spontaneous reporting system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 16 publications
1
27
0
2
Order By: Relevance
“…So, our results did not show any site‐specific issue nor did they show any type of CT issue as we used data from different types of CT. Moreover, this issue of completeness or accuracy in SAE case reports has been identified as an important factor hampering the usefulness of SAE case reports not only in CT but also in post‐marketing pharmacovigilance . Direct comparison between our results and other published data is not easy because criteria used are different, nethertheless; results go in the same way.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…So, our results did not show any site‐specific issue nor did they show any type of CT issue as we used data from different types of CT. Moreover, this issue of completeness or accuracy in SAE case reports has been identified as an important factor hampering the usefulness of SAE case reports not only in CT but also in post‐marketing pharmacovigilance . Direct comparison between our results and other published data is not easy because criteria used are different, nethertheless; results go in the same way.…”
Section: Discussionmentioning
confidence: 83%
“…Although SAE case reports are the main way of monitoring safety in CTs, there is little information available about their quality . On the contrary, in post‐marketing pharmacovigilance, lack of quality of AE case reports is a known problem …”
Section: Introductionmentioning
confidence: 99%
“…In the study of Gedde-Dahl et al [16], the characteristics and the quality of ADR reports of the pharmacists were evaluated in comparison to the reports of the physicians. The spectrums of the reported drugs were especially different from the ones in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study we found about 50% of the adverse events identified in RCTs such as nausea and diarrhoea could be detected from the FDA spontaneous reporting database. Other studies have also found that non-serious adverse events are commonly reported to spontaneous reporting databases [40][41][42]. Similarly, in administrative claims data, medicines used to treat adverse events may not always be recorded.…”
Section: Discussionmentioning
confidence: 99%